Edukasi Pencegahan Kegawatdaruratan Hipertensi Pada Lansia - Oscar Ari Wiryansyah; Indra Wahyudi; Stephanie Pratiwi Sorongan; Rista Dwita (JURNAL PENGABDIAN KADER BANGSA, 2025)
High blood pressure is a disease in which the pressure in the blood vessels increases permanently. Clinically, hypertension can be defined as an increase in blood pressure above the limits set in a guideline. Older people are at high risk of developing high blood pressure because hormonal and biochemical factors play an important role in the development of high blood pressure. Hormonal changes can increase relative androgen levels, increase renin, plasma endothelin, salt sensitivity and insulin resistance, sympathetic activity, body weight, and ultimately hypertension. The goal of this charitable activity is to expand the knowledge of older people so that they can prevent high blood pressure emergencies and maintain their health. The PKM implementation method is based on a community-based research approach that actively involves the elderly, health cadres and sub-district personnel in the prevention, implementation and evaluation of health promotion programs. The results of this activity show that the community-based health promotion approach succeeded in increasing knowledge and changing the attitudes of older people and residents towards the prevention of hypertension emergencies. This improvement was achieved through an approach in the teaching material provided that made the program more relevant and interesting for participants and excited them to take part in the activities.